A Nanoindentation Study of Attenuation in Geological Materials - Nir Z. Badt; Ron Maor; David L. Goldsby (Earth and Space Science)
Abstract The dissipation of elastic strain energy, or attenuation, in Earth materials contributes to a range of geophysical phenomena, such as the damping of seismic waves and tidal heating of planetary bodies. We present a new method for measuring attenuation in single crystals of minerals and in reference materials over a frequency range of 1–10−4 Hz via nanoindentation. In the experiments, we measure the phase lag between a sinusoidal load applied to the nanoindenter tip and the sinusoidal displacement of the tip into and out of the tested sample, which provides a measure of the inverse quality factor Q−1, or attenuation, of the sample. Experiments were conducted on polymethyl methacrylate (PMMA), indium, halite, olivine and quartz. Attenuation spectra from our tests on PMMA and indium are in excellent agreement with reported values from previous studies. We quantified the natural damping of the nanoindenter and showed that it becomes comparable to that of the samples only at frequencies greater than 0.1 Hz, and is much less than that of the samples at frequencies below 0.1 Hz.